Herramientas de Conocimiento y Aprendizaje: Una Guía para Organizaciones Humanitarias y de Desarrollo - and Ramalingam, Ben (ODI, 2006)
This toolkit presents entry points and references to the wide range of tools and methods that have been used to facilitate improved knowledge and learning in the development and humanitarian sectors.
Keywords: spanish